KOMUNIKASI TERAPEUTIK PERAWAT DALAM TERAPI PADA PASIEN SCHIZOPHRENIA PARANOID DI RUANG SIAK DAN INDRAGIRI RUMAH SAKIT JIWA TAMPAN - Arum Wulan Sari; Nova Yohana (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Schizophrenia is a mental health problem in various countries, including Indonesia. In Pekanbaru, based on data obtained from the Tampan Mental Hospital Medical Record, there was an increase in outpatients and inpatients at the Tampan Mental Hospital, where the most cases from year to year were Paranoid Schizophrenia. There are three therapies performed by nurses to treat Paranoid Schizophrenia patients in Siak Room and Indragiri Room at the Tampan Mental Hospital. First, by pharmacological therapy. Second, with nursing care and third, with group activity therapy based on the planned Implementation Strategy. The three therapies use therapeutic communication in its activities.This study aims to determine the therapeutic communication process in pharmacological therapy, nursing care and group activity therapy in Siak Room and Indragiri Room at the Tampan Mental Hospital. The method in this study is qualitative which describes the purpose of the study and is interpreted narratively. The informants in this study were 3 Nurses from Siak Room, 3 Nurses from Indragiri Room, Heads of Siak Room, Heads of Indragiri Room, 2 Patients from of Siak Room, 2 Patients from Indragiri Room and Heads of Psychiatric Nursing Departments with a purposive technique. Data collection techniques used were observation, interviews and documentation with the data validity technique using an extension of participation and triangulation.The results showed that in pharmacological therapy, there were four phases in the therapeutic communication used, namely the pre-interaction phase, the orientation phase, the work phase and the termination phase. In nursing care, four phases in therapeutic communication occur in assessment and implementation. Whereas the communication in nursing diagnosis, intervention and evaluation are only written. The nursing care used is hallucinatory management. In the therapy of group activities, Paranoid Schizophrenia patients use perception stimulation therapy. There are five implementation strategies in perception stimulation therapy, namely recognizing hallucinations, controlling hallucinations by rebuking, controlling hallucinations by carrying out activities, controlling hallucinations by conversing and controlling hallucinations by complying with medication. The four phases of therapeutic communication that occur in each implementation strategies. Keywords: Therapeutic Communication, Paranoid Schizophrenia, Therapies